Alcohol and other substance use during the COVID-19 pandemic: A systematic review. (1st December 2021) - Roberts, Amanda; Rogers, Jim; Mason, Rachael; Siriwardena, Aloysius Niroshan; Hogue, Todd; Whitley, Gregory Adam; Law, Graham R.
Abstract: Background: Although evidence suggests substance and alcohol use may change during the Covid-19 pandemic there has been no full review of the evidence around this. Methods: A systematic review of all available evidence was carried out to document and interpret the frequency and severity of alcohol and other substance use during the Covid-19 pandemic and their relationship to demographic and mental health variables that may suggest further clinical implications. Peer reviewed articles in MEDLINE, Embase, PsycINFO, CINAHL complete and Sociological Abstracts were searched from December 2019 until November 2020. Results: The search and screening identified 45 articles from 513 deduplicated records. The evidence suggests a mixed picture for alcohol use. Overall, there was a trend towards increased alcohol consumption. The proportion of people consuming alcohol during the pandemic ranged from 21.7% to 72.9% in general population samples. Unlike alcohol use, there was a clear trend towards increased use of other substances use during the COVID-19 pandemic. The proportion of people consuming other substances during the pandemic ranged from 3.6% to 17.5% in the general population. Mental health factors were the most common correlates or triggers for increased use of both alcohol and other substances. Conclusion: There is an increased need for treatment for alcohol and other substance use related problems during the pandemic. Increased targeting and evidence-based interventions will also be important in the period which follows this pandemic, to improve the quality of life for individuals and families, but also to prevent additional costs to society and health systems. Highlights: There is a trend towards increased alcohol consumption and increased use of other substances during the pandemic. The most common specific mental health disorder linked to increased use was depression. Anxiety, hopelessness, and social isolation were also observably related to increases in use.